METHODOLOGY FOR TEACHING FOREIGN LANGUAGES - NashirovaDilnozaBuriyevna (Western European Studies, 2024)
This article reviews the current methodologies used in teaching foreign languages and assesses their effectiveness based on recent research findings. A comprehensive literature review was conducted to identify the most commonly used teaching methods. Quantitative data on learning outcomes was collected from 25 studies evaluating different methodologies. The results show that immersive, communicative approaches that prioritize authentic language use and student interaction tend to produce the best outcomes in terms of proficiency gains.
Keywords: foreign language teaching; methodology; second language acquisition